Impact of insecticides on Brevicoryne brassicae (L.) and its influence on broccoli yield in Guaytacama, Cotopaxi, Ecuador: Agricultura y Silvicultura - Ugsha Sabando , José Gabriel (2024)
Broccoli (Brassica oleracea var. italica) is an important vegetable due to its nutritional value and for Ecuador it constitutes an export crop. Its cycle can be affected by pests such as the cabbage aphid, Brevicoryne brassicae (L.) (Hemiptera: Aphididae) that, by extracting the photoassimilates, can damage the flower head causing loss of its commercial value. These pests are treated with organo-synthetic insecticides but their application can generate ecological imbalances, and insect resistance to pesticides. This research aimed to evaluate the effect of insecticides on B. brassicae populations and crop yield. In Guaytacama, Cotopaxi, a plot (1600 m2) was planted, divided into four complete blocks at random, including 13 treatments: azadirachtin (doses: 1000, 1500 and 2000 mL·ha-1), Sophora extract (doses: 600, 800 and 1000 mL·ha-1), lambdacyalothrin (doses: 200, 250 and 300 mL·ha-1), azadirachtin + capsaicin + allicin (doses; 2000, 2500 and 3000 mL·ha-1) and untreated check. The number of aphids, control effectiveness and yield (t·ha-1) were evaluated. The results showed smaller aphid populations (3.5-4.4 individual), higher efficiency (94.5-98.7%) and higher yield (18.5-19.7 t·ha-1) in lambdacyhalothrin (dose: 300 mL), in azadirachtin + capsaicin + allicin (dose: 3000 mL) and in Sophora extract (dose: 1000 mL). The effectiveness controlling B. brassicae and high yields detected in botanical insecticides make their use promising for the sustainable management of pests in this important export crop of Ecuador.